An Affordance-Based Design Model for Interactive Screens to Trigger User Driven Actions in Self-Service Restaurants - Khursheed, Muhammad Ismail (My University, 2025)
This thesis, An Affordance-Based Design Model for Interactive Screens to Trigger User Driven Actions in Self-Service Restaurants, presents an affordance-based design model for interactive screens in public self service restaurants (SSRs). As interactive displays become increasingly prevalent in public settings, designers and engineers face significant challenges in creating interfaces that effectively capture attention, communicate information, and influence user-driven actions in environments characterized by diverse user populations, cognitive overload, and varying contextual factors. Drawing on affordance theory, human-computer interaction principles, and persuasive technology research, this study develops an introductory model that systematically addresses these challenges through the integration of visual, perceived, contextual, and interaction affordances. The model is then validated through three progressive experiments conducted at Flavoria, a university self-service restaurant in Turku, Finland. Each experiment explores different levels of communication for user engagement: passive communication through a rush meter display, active input via an animated polling interface, and two-way communication through an interactive food waste pledge system. Data collected from these experiments, including interaction metrics demonstrated the model's effectiveness in achieving engagement rates of 5-10\% among diners, which represents a notable success rate for public interactive displays. The primary contribution of this research is an introductory quantifiable model for measuring and optimizing affordances in interactive screen design. It provides designers and engineers with a systematic approach to creating more effective interactive displays. The model bridges theoretical concepts with practical design guidelines, offering both a mathematical model for affordance measurement and a structured application process for implementation. In addition, this research explores how to utilize this model for designing different levels of communication on interactive screens to support user-driven actions. This research advances our understanding of how affordance-based design can be utilized for user engagement and trigger actions in public interactive screens, contributing to both the theoretical discourse on affordances and the practical side of human-computer interaction.
Keywords: affordance theory, human-computer interaction, interactive displays, public dining spaces, food sustainability, user engagement, design model, self service restaurants, mathematical model